2000
DOI: 10.1185/0300799009117005
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension Control in the Elderly with Amlodipine

Abstract: Treatment of hypertension in the elderly reduces the incidence of cardiovascular events. Some classes of antihypertensive drugs, including long-acting dihydropyridine calcium channel blockers such as amlodipine, can be prescribed in the presence of comorbid conditions. The results of clinical trials support the use of long-acting dihydropyridine calcium channel blockers in the elderly; amlodipine has been shown to be effective and well tolerated in the elderly population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…30 It can be prescribed in the comorbid conditions of hypertension. 31 However, literature suggests variable effect of amlodipine in patients of heart failure. 32 Recently one study suggest low dose aspirin do not effective as primary prevention of cardiovascular diseases and increases the risk of major haemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…30 It can be prescribed in the comorbid conditions of hypertension. 31 However, literature suggests variable effect of amlodipine in patients of heart failure. 32 Recently one study suggest low dose aspirin do not effective as primary prevention of cardiovascular diseases and increases the risk of major haemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…Elderly patients with hypertension have an associated increased incidence of both mortality and morbidity, such as cerebro‐vascular accidents, cardiac failure and renal insufficiency 5 . There is, as yet, no definitive data to prove beyond doubt that treatment of such patients will improve their prognosis but a review of the information available would suggest that therapy is beneficial 1 . It is important to note however that those trials yet to report definitive endpoints are able to confirm that treatment is not associated with undue risk 6 …”
Section: Discussionmentioning
confidence: 99%
“…Review of the current data suggests that treatment of elderly patients with hypertension is beneficial 1 for both the Veterans Administration Study 2,3 and the Hypertension Detection and Follow‐Up Programme 4 have shown a reduction in end points in those patients treated systematically.…”
Section: Introductionmentioning
confidence: 99%
“…Both of these DHP compounds are better known as L-type calcium channel blockers and are used commonly in the clinic for cardiovascular disorders. Nimodipine is prescribed for delayed cerebral ischaemia following subarachnoid haemorrhage [ 27 ], whereas amlodipine is used as a once-daily oral antihypertensive agent particularly in the aged patient [ 28 ]. However, there have been no focussed studies on the side-effects of these L-type calcium channel blockers in patients of American Black origin and where the possibility of functional P2X5 receptors has to be taken into account.…”
Section: Human P2x5 Receptorsmentioning
confidence: 99%